Capillary electrophoretic focusing of covalently derivatized protein induced by surfactant. Issue 9 (30th March 2016) - Oukacine, Farid; Quirino, Joselito P.; Mesbah, Kiarach; Taverna, Myriam
Abstract : In this communication, we present a very simple strategy to focus covalently derivatized proteins for high sensitivity CE analysis by LIF detection. We demonstrated that the covalently tagged protein can be focused just by adding SDS at a concentration above the CMC in the derivatized sample. Under specific injection conditions, SDS concentration below the CMC is also sufficient to induce the focusing of the tagged protein. This method allows the quantification and detection of the covalently tagged protein in a narrow zone with an efficiency approaching 220 000 plates/m. Very good linearity was obtained for the ubiquitin in a concentration range of 2–25 μM.